2020
DOI: 10.1039/c9ra10063f
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of ZIF-8 nanoparticles into 3D nitrogen-doped hierarchically porous carbon for Li–S batteries

Abstract: A novel transformation strategy assisted with ammonia treatment was successfully developed to fabricate ZIF-8-derived nitrogen-doped hierarchically porous carbon (NHPC/NH3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…[28] Likewise, LiPSs are unlikely to diffuse into the ultramicropores of NC/wG (pore diameter < 7 Å, Figure S3, Supporting Information), resulting in similar conversion kinetics as NC/G. [26a] It is also important to note that the difference in nitrogen content between wG and G mainly comes from the different concentration of graphitic-N (Figure 1c and Figure S5c, Supporting Information), which has considerably weak LiPS adsorption binding energy compared to pyridinic-N and pyrrolic-N. [29] In addition, all the graphenebased materials in Li 2 S 6 show similar polysulfide adsorption capabilities (Figure S14, Supporting Information). [11d] Therefore, it can be concluded that both ultramicroporosity and the difference in nitrogen content are not major contributors to the increased kinetics of FeNC/wG compared to FeNC/G.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…[28] Likewise, LiPSs are unlikely to diffuse into the ultramicropores of NC/wG (pore diameter < 7 Å, Figure S3, Supporting Information), resulting in similar conversion kinetics as NC/G. [26a] It is also important to note that the difference in nitrogen content between wG and G mainly comes from the different concentration of graphitic-N (Figure 1c and Figure S5c, Supporting Information), which has considerably weak LiPS adsorption binding energy compared to pyridinic-N and pyrrolic-N. [29] In addition, all the graphenebased materials in Li 2 S 6 show similar polysulfide adsorption capabilities (Figure S14, Supporting Information). [11d] Therefore, it can be concluded that both ultramicroporosity and the difference in nitrogen content are not major contributors to the increased kinetics of FeNC/wG compared to FeNC/G.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The mesopores and micropores can make sulfur highly dispersed in HPCNFs and effectively inhibit the shuttle effect to reduce the loss of sulfur through physical adsorption (Wang et al, 2021b). The mesopores accelerate the transfer rate of lithium ions (Cao et al, 2020). The result will improve the capacity and cycling stability of the HPCNFs@S electrode.…”
Section: Structural and Morphological Characterizationsmentioning
confidence: 97%
“…At present, a large number of studies have shown that metal-organic frameworks (MOFs) can provide rich pore structures after carbonization, and the pore size of MOFs is easier to control due to the diversity of self-assembly forms of central metal ions and organic ligands (Wang et al, 2014;Skoda et al, 2019;Fang et al, 2021). This contributes to provide more room for accommodating sulfur to prevent the dissolution of polysulfides and enhance cyclic stability (Cao et al, 2020). In general, ZIFs-8 (zeolitic imidazolate frameworks) as a typical MOF material with a high specific surface area can be used as a pore-making template to adjust the size of the internal pore structure of carbon nanofibers (Liu et al, 2017;Chang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that heteroatom doping such as B, N, O, P, and S is an effective strategy to enhance the physicochemical property of carbon matrix. (Liu et al, 2017;Song et al, 2017;Chang et al, 2018;Cao et al, 2020;Fang et al, 2021;Cao et al, 2022) On the one hand, heteroatom doping is efficient in introducing defects in carbon materials, and further provide more active sites for K + storage. (Zeng et al, 2014;Yao et al, 2021;Zhou et al, 2021) On the other hand, the doping elements can also increase the conductivity, expand the interlayer distance of carbon based materials, thus imparting outstanding electrochemical performance to the carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…(Zeng et al, 2014;Yao et al, 2021;Zhou et al, 2021) On the other hand, the doping elements can also increase the conductivity, expand the interlayer distance of carbon based materials, thus imparting outstanding electrochemical performance to the carbon materials. (Zeng et al, 2014;Liu et al, 2017;Song et al, 2017;Chang et al, 2018;Cao et al, 2020;Fang et al, 2021;Yao et al, 2021;Zhou et al, 2021;Cao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%